MicroRNA-181b regulates NF-κB–mediated vascular inflammation - Sun, Xinghui; Icli, Basak; Wara, Akm Khyrul; Belkin, Nathan; He, Shaolin; Kobzik, Lester; Hunninghake, Gary M.; Vera, Miguel Pinilla; Blackwell, Timothy S.; Baron, Rebecca M.; Feinberg, Mark W. (The Journal of clinical investigation, 2012)
EC activation and dysfunction have been linked to a variety of vascular inflammatory disease states. The function of microRNAs (miRNAs) in vascular EC activation and inflammation remains poorly understood. Herein, we report that microRNA-181b (miR-181b) serves as a potent regulator of downstream NF-κB signaling in the vascular endothelium by targeting importin-α3, a protein that is required for nuclear translocation of NF-κB. Overexpression of miR-181b inhibited importin-α3 expression and an enriched set of NF-κB-responsive genes such as adhesion molecules VCAM-1 and E-selectin in ECs in vitro and in vivo. In addition, treatment of mice with proinflammatory stimuli reduced miR-181b expression. Rescue of miR-181b levels by systemic administration of miR-181b "mimics" reduced downstream NF-κB signaling and leukocyte influx in the vascular endothelium and decreased lung injury and mortality in endotoxemic mice. In contrast, miR-181b inhibition exacerbated endotoxin-induced NF-κB activity, leukocyte influx, and lung injury. Finally, we observed that critically ill patients with sepsis had reduced levels of miR-181b compared with control intensive care unit (ICU) subjects. Collectively, these findings demonstrate that miR-181b regulates NF-κB-mediated EC activation and vascular inflammation in response to proinflammatory stimuli and that rescue of miR-181b expression could provide a new target for antiinflammatory therapy and critical illness.